A dual-sensitized luminescent europium(iii) complex as a photoluminescent probe for selectively detecting Fe3+. Issue 41 (25th June 2020) - Zhao, Yafeng; Xu, Yanhong; Xu, Bing; Cen, Peipei; Song, Weiming; Duan, Lijuan; Liu, Xiangyu
Abstract : A stable dual-sensitized Eu(iii )-complex constructed with two different ligands can be used as a sensing platform for Fe 3+ detection. Abstract : A new luminescent Eu III complex, namely [Eu2 (BTFA)4 (OMe)2 (dpq)2 ] (1 ), in which BTFA = 3-benzoyl-1, 1, 1-trifluoroacetone and dpq = dipyrido [3, 2- d :2′, 3′- f ] quinoxaline, has been designed and synthesized by employing two different ligands as sensitizers. Crystal structure analysis reveals that complex 1 is composed of dinuclear Eu III units crystallized in the monoclinic P 1̄ space group. Notably, 1 exhibits high thermal stability up to 270 °C and excellent water stability. The photoluminescence property of the complex is investigated. Further studies show 1 can recognize Fe 3+ ions with high selectivity from mixed metal ions in aqueous solution through the luminescence quenching phenomenon. Furthermore, the recyclability and stability of 1 after sensing experiments are observed to be adequate. By virtue of the superior stability, detection efficiency, applicability and reusability, the as-prepared Eu III complex can be a promising fluorescent material for practical sensing.